ESTIMULACIÓN ELÉCTRICA DE CANALES DE ALPACAS PARA MEJORAR SU CALIDAD ORGANOLÉPTICA - Guerrero M., Oscar (2004)
Electrical stimulation is a technique that may reduce the lenght of maturity, rigor mortis and acidity of meat, as well as improving sensory characteristics. The objetive of the study was to show that the electrical stimulation has a significant effect on the quality of alpaca meat such as tenderness, juiceness, flavor, odor and sanitary condition. Twelve female alpacas from 4 to 5 year old and 50-60 kg of body weight were used. They were slaughtered and electrically stimulated 60 minutes later using electrodes on muscular tissue. All half carcasses were stimulated with 500 v per 60 s (T1), 500 v per 30 s (T2), 600 v per 60 s (T3), and 600 v per 30 s (T4). All other half carcasses were kept without electrically stimulation. The results indicated that the electrical stimulation had a significant effect (p=0.00) on the pH alpaca meat reducing microbial growth 24 h after stimulation (p=0.004), where treatment T2 (500 v/60s) showed the best effect. The evaluation of sensory characteristics showed a significant effect for odor on treatment T1 (p=0.009), flavor on treatment T4 (p=0.002), tenderness on treatments T2 (p=0.023) and T3 (p=0.004), and juiceness on treatment T4 (p=0.005).